Measuring organisation capital at the firm level: A production function approach - Christian Rammer; Felix Roth; Markus Trunschke (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Organisation capital is one of the key intangible assets of firms, driving innovation and firm performance. Measuring this asset has been notoriously difficult, however. Differently to other intangible assets, firms do not build up organisation capital primarily by monetary investment but rather through establishing new organisational routines and building up trust, which often do not coincide with any financial expenditure. Quantifying such efforts at the firm level has largely failed so far. This paper takes up a traditional production function approach which includes, in addition to labour and tangible assets, investment in all measurable intangible assets (technological and non-technological knowledge, software and databases, firm-specific human capital, brand equity), but excluding organisation capital. The residuum of the estimation is considered as a measure of a firm' organisation capital. Using panel data from the German innovation survey, we find higher organisation capital in young and small firms. Our measure tends to show a u-shaped link to qualitative indicators such as organisational innovation.
Keywords: D24; E22; L25; 330; Organisation Capital; Production Function; CIS